Who Does Not like Migrants? Individual Demographics and Attitudes Towards Migration - Sandra V. Rozo; Maria J. Urbina (Institute of Labor Economics (IZA), 2020)
We exploit the quasi-random settlement of refugees in Sweden between 1985 and 1994 to examine the characteristics of individuals showing a disproportionate negative response to migration flows and whether these responses differ when the arrival of refugees occurred concurrently with economic shocks. We document that, on average, migration shocks translate to lower support for immigration. These responses are disproportionately driven by the changes in attitudes of young males, with less wealth, and who work in blue-collar occupations. Also, we find more support for immigration where employment increased and tax collection was lower concurrent with the arrival of refugees.
Keywords: D72; F2; O15; R23; 330; migration; attitudes; demography